Sistem Monitoring Pintu Air Bendungan Menggunakan Mikrokontroler Wemos D1 R1 Berbasis Website - Yerry Febrian Sabanise; Rais (Journal of Innovation Information Technology and Application (JINITA), 2019)
Floodgate monitoring is related to water level monitoring. Problems that occur Weir information about the water level, water runoff, level, status of floodgates and recap results that can be seen on the web in real-time are not yet available, so monitoring the floodgates is difficult, less effective and maximum. Weir officials must go back and forth from the weir to the guard post and then to the control to move the floodgates. The purpose of the design of a sluice monitoring system is based on the website. Assist officers in monitoring floodgates to make it more effective and maximal. Using Wemos D1 R1 Microcontroller, Ultrasonic Sensor HC-SR04 to read water level, DC Motor moves the floodgates. LCD displays runoff and level. Siren as a danger warning. The trial results show that the system that has been made runs well. The system is able to open the floodgates through control of the web and runs automatically. Water runoff and level can be displayed on the LCD. Weir information about water levels, water runoff, levels, sluice status, and recap results can be viewed on the web in real time.